The Urgency of Ethics in Islamic Business For The Onlineshop Seller in E-Commerce - Yulia Kurniaty (Justicia Islamica, 2019)
This work aims to examine the responsibility of online shop sellers from the perspective of Islamic business ethics. This issue is urgent to discuss because the transformation of transactions between sellers and buyers in e-commerce has an impact on the behavior of the sellers who often ignore the rights of the buyers, such as sending goods that are not according to the order, hidden defects for the sent goods, the unfriendly behavior of the sellers, etc. The method used to answer the problem is a literature study that discusses Islamic business ethics, the study material obtained then reduced and analyzed using the logic of deductive thinking. The results show that several online shop sellers did not serve consumers well according to business ethics in Islam, such as not answering chat with polite sentences, sending goods that were not according to the order, items sent hid some defects or packing and shipping processes for the item is often too long. For this reason, the responsibility of the online shop seller is to guarantee the availability of goods, the goods delivered according to the agreement at the time of booking, to provide an explanation of the estimated length of delivery of goods, to provide order returns, and no fees, and to serve buyers politely.Tulisan ini bertujuan mengkaji bagaimana tanggung jawab penjual onlineshop dalam pandangan etika bisnis Islam. Topik ini perlu dikaji karena beralihnya transaksi antara penjual dengan pembeli ke media e-commerce berdampak pada perilaku penjual yang seringkali mengabaikan hak-hak pihak pembeli. Misalnya mengirimkan barang yang tidak sesuai pesanan, barang dikirim namun terdapat cacat tersembunyi atau dikirim namun terlambat sampai ke konsumen, melayani konsumen via chat tidak ramah. Metode yang digunakan adalah studi pustaka yang membahas etika bisnis Islam, bahan kajian yang diperoleh lantas direduksi kemudian dianalisis dengan menggunakan logika berpikir deduktif. Hasil penelusuran penulis di beberapa seller online shop menemukan realita bahwa beberapa dari mereka tidak melayani konsumen dengan baik sesuai etika bisnis dalam Islam seperti tidak menjawab chat dengan kalimat yang santun, mengirimkan barang tidak sesuai pesanan, barang yang dikirim terdapat cacat tersembunyi atau proses pengepakkan dan pengiriman barang terlampau lama. Untuk itu tanggungjawab penjual online shop adalah menjamin ketersediaan barang, barang yang dikirimkan sesuai kesepakatan saat pemesanan, memberikan penjelasan mengenai estimasi lama waktu pengiriman barang, menyediakan layanan retur order dan tanpa biaya, serta melayani pembeli dengan santun.